Penatalaksanaan Fisioterapi Dengan Pendekatan Neuro Developmental Treatment Pada Kasus Cerebral Palsy Spastic Diplegi Di Pntc Karanganyar - Luhur, Ajeng Tuladani Mangerthi, Edi Waspada, SST.FT., S.Fis., M.Kes (2016)
Background : Cerebral Palsy is a group of conditions affecting motor funtion as a result of damage to the brain. Cerebral Palsy Spastic Diplegi have problem in to disorders of movement and posture due to a non-progressive lesion as a result of injury to the central nervous system. All four limbs are affected, but legs more than arms. Lower extremity (leg) will undergo hypertonus or stiffness in the muscles so that the movement becomes stiff. Objective: To know the benefit of neurodevelopmental trearment (NDT) to achieve a goal of physiotherapy in the form of inhibition in reducing spasticities and facilitation to enhance the functional activity of the cerebral palsy condition. Result : the result obtained after the conducted theraoy 6 times are as follow no decrease or increase spasticity by asworth scale T1: fleksor hip 0, ekstensor hip 0, fleksor knee 1, ekstensor knee 0, plantar fleksor ankle 0, dorsal fleksor ankle 3 menjadi T6: fleksor hip 0, ekstensor hip 0, fleksor knee 1, ekstensor knee 0, plantar fleksor ankle 0, dorsal fleksor ankle 3. Functional activity by GMFM T1: total score 46,6% intoT6: 46,6%. Conclution : no change in either an increase or decrease in spasticity and capabilities of functional activity.